Electrochemistry in Archaeology and Art Conservation. Issue 1 (16th November 2020) - Doménech‐Carbó, Antonio
Abstract: Electrochemical techniques are of application in the fields of archaeometry, conservation and restoration of cultural heritage. These include the identification of components in paintings, ceramic and glasses, fibers, metals, etc., but also establishing diagnostic criteria of conservation and the application of conservative treatments. Here, it is presented an updated summary of the evolution of these applications in the last decades, and a discussion on their capabilities and future research for tracing, authentication, manufacturing techniques, provenances, and dating. Abstract :